Vitamin D Status Is Negatively Related to Insulin Resistance and Bone Turnover in Chinese Non-Osteoporosis Patients With Type 2 Diabetes: A Retrospective Cross-Section Research - Jie Zhang; Jie Zhang; Yangjun Li; Dong Lai; Di Lu; Zhenhao Lan; Junfei Kang; Yidong Xu; Shaofang Cai (Frontiers Media S.A., 2022)
Background and ObjectivesVitamin D status is closely related to blood glucose and bone metabolism in patients with type 2 diabetes (T2DM). Vitamin D affects bone density and bone metabolism, leading to osteopenia and osteoporosis. Insulin resistance increases the risk of osteoporosis in patients with T2DM. Our previous studies have shown a negative correlation between insulin resistance and 25-hydroxy vitamin D [25(OH)D] levels. The aim of the present study was to determine the association between vitamin D status and insulin resistance and bone metabolism in patients with T2DM.Subjects and MethodsA retrospective cross-section research was carried out among 109 non-osteoporosis patients with T2DM. Their fasting blood glucose (FBG), 25(OH)D, fasting blood insulin (FINS), glycosylated hemoglobin (HbA1c), serum creatinine (SCr), calcium (Ca), phosphorus (P), insulin-like growth factor-1 (IGF-1), bone alkaline phosphatase (BALP), body mass index (BMI), glomerular filtration rate (eGFR), homeostatic model estimates of insulin resistance (HOMA-IR), and calcium-phosphorus product were measured routinely.ResultsBoth in men and women, 25(OH)D was negatively correlated with BALP (β = −0. 369, p ≤ 0.001)and HOMA-IR (β = −0.349, p ≤ 0.001), and positively associated with IGF-1(β = 0.672, p ≤ 0.05). There was a negative correlation between HOMA-IR and IGF-1 (β = −0.464, p ≤ 0.001), and a positive correlation between HOMA-IR and BALP (β = 0.344, p ≤ 0.05), adjusted by confounding factors.ConclusionOur study demonstrates that 25(OH)D concentrations are negatively correlated with insulin resistance and bone turnover. Insulin resistance increases with the decrease of 25(OH)D concentration, which can enhance bone turnover, and increases the risk of osteoporosis in non-osteoporosis patients with T2DM. This is the first study to clarify the relationship between serum vitamin D status, insulin resistance, and bone metabolism in non-osteoporosis patients with T2DM in China.